OPTIMIZATION OF LOADING MODES OF A CONTROLLED ASYNCHRONOUS ELECTRIC DRIVE - L.N. Kanov (National Technical University "Kharkiv Polytechnic Institute", 2013)
The paper introduces a numerical procedure of an asynchronous motor optimum frequency and feed sine-wave voltage selection for given values of the motor speed and load moment to provide minimum power loss